On walls, on clothing, on the skin: the character in the urban landscape (Comunicação & Inovação, 2016)
This article discusses the different ways of exhibiting images of comic book characters in the urban environment. In spite of copyright rules, these images are unduly displayed in public places. This typeof appropriation aims to spread a wide range of discourses,from political positions to personal accounts.Such discourses are materialized on temporaryand permanent supports: walls, facades, vehiclesand even the human body that moves around thecity. Although these displays are of a subversivenature, these practices reveal creative ways of talkingabout the city and its citizens.
Keywords: Urban environment. Character. Appropriation.